Ideologi Madzhab Fiqih dan Sosial Politik dalam Kaidah Nahwu (Ibnu Madha dalam ar Rad ala al Nuhat) - Rosyidah, Inayatur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
Language can not be separated from socio-cultural elements, and political science, including Arabic and other languages . This study will attempt to link the issue of language with the language issue, whether the pattern outside the political and ideological jurisprudence Ibn Madha an impact on the formulation of rules nahwu and how the relation of language, jurisprudence and politics in the present context. This study includes the type of library research, which uses the resources in the literature discussing the main issues and sub-sub-problems that have been formulated. Ibn Madha’s thought influenced the ideology of fiqh al Dhaheri stream which he embraced in addition to political and social dynamics. Likewise Shiite ideology Nushairiyah an impact on the political complexion Hafiz al Assad and his son in the form of dictatorship in Syria. Thus, language is a symbol of thought and the things of men can be symbolized by language and language as a system of symbols are sometimes used in a wider sense, namely the transformation of language into a tool of ideology, social setting and political upheaval that occurred.